1993
DOI: 10.1021/ma00077a063
|View full text |Cite
|
Sign up to set email alerts
|

A flow-orientation transition in a thermotropic random copolyester

Abstract: Introduction. This paper reports some preliminary results of a study of flow-induced orientation in a series of liquid crystalline polymers based on hydroxybenzoic acid (HBA) and hydroxynaphthoic acid ( "A) units. Previous, in situ studies of orientation in flowing liquid crystalline polymers of this type have shown the development of significant chain orientation in the direction of shear,' as well as the tendency for shear-induced crystallinity at temperatures close to the melting point.2 A recent series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 3 publications
3
19
0
Order By: Relevance
“…In this case, the effective composition f", associated with the statistical segments of blocks measured along the field is equal: j~"'p N. I -f Keller, Pedemonte, and Willmouth [11], Hadziioannou et al [12), Balsara and Hammouda [13], Rorno-Uribe and Windle [14], and Albalak and Thomas [15] studied the alignment of hexagonally cylindrical and lamellar microdomains in diblock copolymers, solvated diblock copolymers, and random copolymers, respectively, under deformations. Le Meur et al [16]reported on a shift of the order-disorder transition temperature by a shear, and Morrison et al [17] have shown that the degree of phase mixing depends on the strain.…”
Section: Reentrant Phase Transitionsmentioning
confidence: 99%
“…In this case, the effective composition f", associated with the statistical segments of blocks measured along the field is equal: j~"'p N. I -f Keller, Pedemonte, and Willmouth [11], Hadziioannou et al [12), Balsara and Hammouda [13], Rorno-Uribe and Windle [14], and Albalak and Thomas [15] studied the alignment of hexagonally cylindrical and lamellar microdomains in diblock copolymers, solvated diblock copolymers, and random copolymers, respectively, under deformations. Le Meur et al [16]reported on a shift of the order-disorder transition temperature by a shear, and Morrison et al [17] have shown that the degree of phase mixing depends on the strain.…”
Section: Reentrant Phase Transitionsmentioning
confidence: 99%
“…15,16 While providing fertile ground for much intriguing materials physics, the structural complexities associated with the coupling of orientation and flow have proven to be factors limiting the ultimate properties of LCPs. [17][18][19][20][21] Thus, the rheological behavior of both thermotropic liquid-crystalline polymers (TLCPs) [22][23][24][25][26][27][28][29][30][31] and lyotropic LCPs [32][33][34][35][36][37][38][39][40][41][42] has been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, a recent report by Windle shows that when the molecular weight of a 75/25 HBA/HNA copolyester increases from 8600 to 30 000, the increase in melting point is only 12°C (from 283 to 295°C). 27 It is unrealistic then to attribute changes of 40°C or more to an increase in molecular weight.…”
Section: Resultsmentioning
confidence: 99%